Design of a Novel Theranostic Nanomedicine (III): Synthesis and Physicochemical Properties of Tumor-Targeting Cisplatin Conjugated to a Hydrophilic Polyphosphazene - Patil BR (Dove Medical Press, 2020)
Basavaraj R Patil,1 Su Yeon Kang,2 Da Hee Jung,2 Prakash G Avaji,1 Yong Joo Jun,1 Hwa Jeong Lee,2 Youn Soo Sohn1 1C & Pharm, Ewha Womans University, Seoul 03760, Republic of Korea; 2Graduate School of Pharmaceutical Sciences, Ewha Womans University, Seoul 03760, Republic of KoreaCorrespondence: Youn Soo SohnC & Pharm, Ewha Womans University, Room 304, University-Industry Cooperation Building, 52 Ewhayeodae-Gil, Seodaemun-Gu, Seoul 03760, Republic of KoreaTel +82 70 7008 2120Fax +82 2 362 8813Email yssohn@ewha.ac.krHwa Jeong LeeGraduate School of Pharmaceutical Sciences, Ewha Womans University, 52 Ewhayeodae-Gil, Seodaemun-Gu, Seoul   03760, Republic of KoreaTel +82 2 3277 3409Fax +82 2 3277 2851Email hwalee@ewha.ac.krPurpose: A new theranostic nanomedicine involving anticancer-active cisplatin moiety was designed to study its tumor-targeting properties as well as its drug efficacy and toxicity.Methods: A cisplatin carrier polymer was prepared by grafting equimolar polyethylene glycol of a molecular weight of 550 (PEG550) and aminoethanol to the poly(dichlorophosphazene) backbone. Cisplatin was conjugated to the carrier polymer using cis-aconitic acid as a linker.Results: The cisplatin-loaded polyphosphazene, named “Polycisplatin” was found to be amphiphilic in aqueous solution and self-assembled into nanoparticles with an average particle size of 18.6 nm in diameter. The time-dependent organ distribution study of Cy5.5-labeled Polycisplatin in the A549-tumor-bearing mice exhibited a high tumor selectivity of Polycisplatin by EPR effect despite the relatively small particle size. In order to compare the in vivo efficacy of Polycisplatin and cisplatin, their xenograft trials were performed using nude mice against the human gastric cell line MKN-28. Polycisplatin exhibited slightly less tumor suppression effect compared with cisplatin at the same dose of 1.95 mg Pt/kg, which is the maximum tolerate dose of cisplatin, but at the higher double dose of 3.9 mg Pt/kg, Polycisplatin exhibited a little better efficacy than cisplatin. Furthermore, mice treated with cisplatin at the dose of 1.95 mg Pt/kg exhibited severe body weight decrease by about 25%, while mice treated with Polycisplatin did not show serious body weight decrease even at its double dose of 3.9 mg Pt/kg. Furthermore, kidney indicators including kidney index, BUN, and creatinine values measured displayed that Polycisplatin is much less nephrotoxic than cisplatin.Conclusion: Nanoparticular Polycisplatin was successfully prepared by conjugating cisplatin to a hydrophilic polyphosphazene carrier polymer using the acid-cleavable cis-aconitic acid. Polycisplatin nanoparticles exhibit excellent tumor-targeting properties by EPR effect. The xenograft trials exhibited excellent antitumor efficacy and reduced systemic toxicity of Polycisplatin.Keywords: cisplatin, polyphosphazene, platinum drug, drug delivery, nanomedicine